SYSTEM AND PROCESS FOR IMPROVED SAMPLING FOR PARALLEL LIGHT TRANSPORT SIMULATION (2012)
Embodiments of the present invention are directed to methods and a system that allow for deterministic parallel low discrepancy sampling, which can be efficient processed, and are effective in removing transitionary artifacts that occur in low-dimensional projections generated in low discrepancy sequences. Embodiments of the claimed subject matter further provide improvements upon the low-dimensional projections and thus the visual quality when using the Sobol' sequence for image synthesis.